Source identification and distribution of petroleum hydrocarbons in soil and sediments of The Northern Persian Gulf Coast - Valizadehkakhki, Fatemeh (2013)
The purpose of this study is to use environmental fingerprinting technique and to identify oil spills and their relationship with the oil derived from known oil fields. This is the first comprehensive study on PAHs and n-alkanes distribution as oil spill markers in the Persian Gulf to investigate petroleum contamination in soil and sediment in the three regions identified as sources of oil and gas. Soil and sediment from three provinces in the northern Gulf has been selected. Soil samples (0-10 cm) were collected from rural land, industrial, urban, and agriculture. Sediment samples were collected from intertidal area, 3 offshore and 2 rivers samples were collected. Intertidal sediment was collected using stainless steel spoon from 5 top cm. Offshore sediment samples were collected using VanVeen grab from 10 km into the Gulf. The results indicated that Total PAHs range between 42.76 to 5596.4 ng.g-1 for rural soils, 460 to 1730.4 ng.g-1 for industrial soil, 165.6 to 3442.3 ng.g-1 for urban soil and 57.3 to 3633.5 ng.g-1 for agricultural soils. Polynuclear aromatic hydrocarbons in rural area showed higher concentration than other stations and it is associated with petrogenic input as these sites are located near oil fields and oil transferring pipelines. In addition, the concentrations for sediment showed that TPH is from 184.5 to 2771.8 ng.g-1 dry weight. Analysis of the results and application of biomarker ratios such as MP/P ratio showed that the main source of PAHs input is petrogenic sources. Consequently, most of the pollution in the sampling region belonged to oil spill, crude oil and petroleum products. On the other hand, analysis of the n-alkanes revealed there was principally higher molecular weight and even carbon numbers. Therefore, it indicates that the major contribution of the n-alkanes are related to crude oil and petroleum products and it is not derived from biogenic sources as the number of odd carbon is very low. Additionally, high vanadium concentration reflects an oil spill background to the area, since vanadium is the major heavy metal constituent of crude oil. To conclude, analysis of all components illustrated that contamination in the mentioned region is derived from direct inputs of petroleum products and crude oil to the land and Gulf. Hence, monitoring and long-term investigation to produce a reference profile is a practical tool to verify the contribution of anthropogenic compounds to this environment.